Approach to the knowledge of preservation of pleistocenic bone: The case of a Gomphothere cranium from the site of Tepeticpac, Tlaxcala, Mexico - Luisa Straulino; Luisa Mainou; Teresa Pi; Sergey Sedov; Aurelio López-Corral; Ramón Santacruz-Cano; Alonso Gabriel Vicencio-Castellanos (Revista Mexicana de Ciencias Geológicas)
An almost complete cranium of a gomphoterium found in Tepeticpac, Tlaxcala, was analyzed with X-ray diffraction (XRD), Petrography and Scanning Electron Microscopy with Energy Dispersive Spectroscopy (SEM-EDS) to stablish the transformations of the bone during its burial. The analyses assessed that the bone mineral (bioapatite) had suffered modifications in mineral composition, “crystallinity index”, cell parameters and CO2 content. However, the paleohistological structure of the bone was not significantly affected, although evidence of microbial attack was found in the bone surfaces. The filling minerals of bone macro and micro porosity were also analyzed; its main filling minerals are calcite (micrite and sparite), clays, and minerals of volcanic origin.